2018
DOI: 10.1002/ajp.22882
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phylogenomic analysis reveals a novel cluster of simian endogenous retroviral sequences in Colobinae monkeys

Abstract: Simian retrovirus (SRV) is a type-D betaretrovirus infectious to the Old World monkeys causing a variety of symptoms. SRVs are also present in the Old World monkey genomes as endogenous forms, which are referred to as Simian endogenous retroviruses (SERVs). Although many SERV sequences have been identified in Cercopithecinae genomes, with potential of encoding all functional genes, the distribution of SERVs in genomes and evolutionary relationship between exogeneous SRVs and SERVs remains unclear. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…In contrast, in Theropithecus and Chlorocebus there are also a few proviruses with only 1-2 nt substitutions between the LTRs (unpublished observation), indeed pointing to a lengthy period of germ line activity. Rhinopithecus roxellana SERV integrations with open reading frames were found to be significantly younger than the ones with frame-shift mutations [132]. Furthermore, heterozygous SERV insertions are presumed to be more recent than integrations that have been fixed in a population.…”
Section: Simian Endogenous Retrovirus (Serv)mentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast, in Theropithecus and Chlorocebus there are also a few proviruses with only 1-2 nt substitutions between the LTRs (unpublished observation), indeed pointing to a lengthy period of germ line activity. Rhinopithecus roxellana SERV integrations with open reading frames were found to be significantly younger than the ones with frame-shift mutations [132]. Furthermore, heterozygous SERV insertions are presumed to be more recent than integrations that have been fixed in a population.…”
Section: Simian Endogenous Retrovirus (Serv)mentioning
confidence: 94%
“…Similar to PcEV, SERV, a full-length integrated type D betaretrovirus was first described from a baboon genomic library [38]. Subsequently, a widespread distribution in OWM with a relatively large nucleotide divergence between the viral sequences suggested a relative old age for the proviruses (Table 2) [38,132]. Heterozygous integrations abound, at least in Chlorocebus sabaeus, which suggests that many are so recent that they have not had sufficient time to become fixed in the population [128].…”
Section: Simian Endogenous Retrovirus (Serv)mentioning
confidence: 99%
See 2 more Smart Citations
“…Full length or nearly full length SERV proviral genomes are found in many OWM species, with up to 80, mostly heterozygous, integrations detected in individual monkeys [6]. A variant SERV, col-SERV, with full length integrations and substantial homology to SRV-6 (simian type D retrovirus-6), was reported from the Asian Colobine species Rhinopithecus roxellana and R. bieti, with incomplete proviruses being present in Nasalis larvatus [7]. Phylogenetic analysis suggested that Col-SERV had spread between and integrated in the genome of Colobine ancestors after the separation of Cercopithecinae and Colobinae, which has been estimated to have occurred approximately 16 mya [7,8].…”
Section: Introductionmentioning
confidence: 99%